Microbiome of Trichodesmium Colonies from the North Pacific Subtropical Gyre - Gradoville, Mary R.; Crump, Byron C.; Letelier, Ricardo M.; Church, Matthew J.; White, Angelicque E. (Frontiers in Microbiology, 2017)
Filamentous diazotrophic Cyanobacteria of the genus Trichodesmium, often found in colonial form, provide an important source of new nitrogen to tropical and subtropical marine ecosystems. Colonies are composed of several clades of Trichodesmium in association with a diverse community of bacterial and eukaryotic epibionts. We used high-throughput 16S rRNA and nifH gene sequencing, carbon and dinitrogen (N2) fixation assays, and metagenomics to describe the diversity and functional potential of the microbiome associated with Trichodesmium colonies collected from the North Pacific Subtropical Gyre (NPSG). The 16S rRNA and nifH gene sequences from hand-picked colonies were predominantly (>99%) from Trichodesmium Clade I (i.e., T. thiebautii), which is phylogenetically and ecologically distinct from the Clade III IMS101 isolate used in most laboratory studies. The bacterial epibiont communities were dominated by Bacteroidetes, Alphaproteobacteria, and Gammaproteobacteria, including several taxa with a known preference for surface attachment, and were relatively depleted in the unicellular Cyanobacteria and small photoheterotrophic bacteria that dominate NPSG surface waters. Sequencing the nifH gene (encoding a subcomponent of the nitrogenase enzyme) identified non-Trichodesmium diazotrophs that clustered predominantly among the Cluster III nifH sequence-types that includes putative anaerobic diazotrophs. Trichodesmium colonies may represent an important habitat for these Cluster III diazotrophs, which were relatively rare in the surrounding seawater. Sequence analyses of nifH gene transcripts revealed several cyanobacterial groups, including heterocystous Richelia, associated with the colonies. Both the 16S rRNA and nifH datasets indicated strong differences between Trichodesmium epibionts and picoplankton in the surrounding seawater, and also between the epibionts inhabiting Trichodesmium puff and tuft colony morphologies. Metagenomic sequence analyses suggested that lineages typically associated with a copiotrophic lifestyle comprised a large fraction of colony-associated epibionts, in contrast to the streamlined genomes typical of bacterioplankton in these oligotrophic waters. Epibiont metagenomes were enriched in genes involved in phosphate and iron acquisition and denitrification pathways relative to surface seawater metagenomes. We propose that the unique microbial consortium inhabiting colonies has a significant impact on the biogeochemical functioning of Trichodesmium colonies in pelagic environments.